(untitled) (Fiep Bulletin - online, 2011)
This text has as an objective to show how sports play an important paper in the build up of social organizations, because through them a possibility to re-establish the relation with the other and the environment is generated. Thus is important to limit the way in which the social relations have been constituted from the new physical realities that surround the processes of virtualization and automatization, from this perspective is possible to see how sport and physical activity have become de-humanizating and de integrating social scenarios. An escape from this problem is obtained when the relations that the subject has with his surrounding and with the other are re-contructed through the elements of integration, social and community construction that sport offers. The possibility of social re instituting is possible in the construction of a communal sport, a sport that allows the construction of community.